The American West and the World Transnational and Comparative Perspectives - Lahti, Janne (Taylor & Francis, 2018)
The American West and the World provides a synthetic introduction to the transnational history of the American West. Drawing from the insights of recent scholarship, Janne Lahti recenters the history of the U.S. West in the global contexts of empires and settler colonialism, discussing exploration, expansion, migration, violence, intimacies, and ideas. Lahti examines established subfields of Western scholarship, such as borderlands studies and transnational histories of empire, as well as relatively unexplored connections between the West and geographically nonadjacent spaces. Lucid and incisive, The American West and the World firmly situates the historical West in its proper global context.